เหตุผลของการมีชีวิตอยู่ตามทัศนะพุทธปรัชญา - Klund-ngam, Sanya; Krongcheep, Siriporn; Ponsen, Kitsuchin (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The article objective is to persent the reasons for living in every life differ depending on attitudes, values, learning and needs. most people live according to their feelings, needs, rather than reason and truth, because power of need is desires, comsist of greed, anger, and delusions, due to the ignorance of the truth of life presume to be how we really were born? why we were born? and lived what for? Thus that is a life without aim. Most people spend their day life with nothing not metters or just living from day to day, Because of ignorance. or possessed ignorance. It is makes the mismderstood that living a life with receiving anything that you want is true happiness. Until he found hardships many people ended their lives in pitiful feature. Because he mistakenly thought that substantial matters is not material, Substantial matters is not matters, There living far away in the truth, The truth that the Lord Buddha taught conquered that he was born as a human being with him in a period lifetime